Denudation Process of Crystalline Nappes in a Continental Collision Zone Constrained by Inversion of Fission‐Track Data and Thermokinematic Forward Modeling: An Example From Eastern Nepalese Himalaya. Issue 5 (23rd May 2022) - Nakajima, Toru; Kawakami, Tetsuo; Iwano, Hideki; Danhara, Tohru; Sakai, Harutaka
Abstract: Thermochronological methods were applied to the Higher Himalayan Crystalline (HHC) nappe and the underlying Lesser Himalayan Sequences (LHS) to elucidate the denudation process for the middle‐ and upper‐crust of eastern Nepal over millions of years. Thermochronological inverse modeling was undertaken for new results of fission‐track (FT) age and FT length data of zircon and apatite in order to reconstruct the time‐temperature ( t‐T ) paths in the temperature range of 60–350°C. Eight t‐T paths calculated along the across‐strike section show that the cooling process of the HHC nappe in this study area is characterized by the following three aspects: (a) gradual cooling followed by rapid cooling and subsequent gradual cooling, (b) northward‐younging of the timing of the rapid cooling, and (c) gradual cooling followed by <2 Myr rapid cooling in the frontmost part of the HHC nappe. The observed FT ages and t‐T paths were then compared with those predicted by forwarding thermokinematic modeling. The results of the thermokinematic modeling for the "Flat‐Ramp‐Flat MHT model", in which the HHC and the underlying LHS are denudated in direct proportion to the uplift of rocks transported along the Main Himalayan Thrust (MHT), reproduced the observed t‐T paths and FT ages in eastern Nepal. This indicates that the observed FT ages and t‐T paths reflect a denudation process driven by the movement of the MHT with a flat‐ramp‐flat geometry and that the denudation rate and its spatial distribution have roughly been constant in eastern Nepal since ca. 9 Ma. Plain Language Summary: Motion of the deep‐seated rocks toward earth's surface (exhumation/denudation) in continental collision zones is a key phenomenon to understanding the mechanism of mountain building associated with a continental collision. Thermochronological method enables us to reconstruct the cooling history of the rock samples and address their denudation history of them. In this study, we collected metamorphic rocks from eastern Nepal and succeeded in reconstructing a detailed cooling history. The observed cooling history was compared with the predicted cooling history derived from numerical modeling of three different denudation processes. As a result, the observed cooling history in eastern Nepal was explained well by denudation associated with the movement of a stable, single plate‐boundary fault. This indicates that the denudation style of the deep‐seated rocks in eastern Nepal was established about 9 million years ago and remained unchanged since then. This finding contributes to understanding mountain building process that affects shallow crustal levels. Key Points: Inversion of fission‐track data and forward thermokinematic modeling were applied to reconstruct the denudation history of eastern Nepal Observed gradual‐rapid‐gradual cooling time‐temperature paths were reproduced by the model assuming the flat‐ramp‐flat structure of the MHT Our result indicates that the denudation pattern has roughly been constant in southeastern Nepal since ca. 9 Ma